STRATEGIES OF COGNITIVISM AND LINGUOCULTUROLOGY IN ENGLISH AND KARAKALPAK PROVERBS - Kurbanbaev Djavod Aminbaevich (Bright Mind Publishing, 2025)
The article traces how cognitivism and linguoculturology formed and developed as complementary approaches, using English and Karakalpak proverbs as a shared empirical field. Conceptual Metaphor Theory provides the mapping procedure (e.g., OPPORTUNITY–HEAT in “Strike while the iron is hot” / Temirdi qizg'anda bas), while linguoculturology adds value-oriented cultural commentary. Drawing on verifiable bilingual compilations, the study examines full, partial, and functional non-equivalences, with attention to Latin-script Karakalpak forms. It shows that universal cognitive frames (time as resource, prudence, collaboration) are realized through culture-specific imagery (craft, fauna, metals) and numeric heuristics. The narrative also outlines practical strategies that supported the field’s growth: systematic mapping, ethnographic framing, corpus building, and orthographic standardization. Pedagogical implications include concept-first explanations and equivalence matrices for contrastive teaching. The article argues that proverb analysis is an effective laboratory for observing the co-evolution of thought and culture in linguistic meaning.
Keywords: Cognitivism; linguoculturology; conceptual metaphor; cultural linguistics; cultural scripts; paremiology; Karakalpak proverbs; English proverbs.